Bonding and bridging: Leveraging immigrant and refugee community assets to support healthy eating. Issue 2 (15th March 2018) - Bloom, J. Dara; Hardison-Moody, Annie; Schulman, Michael
Abstract: Studies of acculturation show that immigrants/refugees who fully adapt to US diets have worse health outcomes than those who remain socially isolated; however, social isolation limits access to resources. We combine a bi-directional model of acculturation with the community capitals framework, suggesting improved outcomes when immigrant/refugee communities maintain healthy traditions from their home countries through bonding social capital, while accessing resources through bridging social capital to practice those traditions in the US context. We apply this lens to a research/outreach project that worked with two immigrant/refugee communities in North Carolina. Facilitating communities' bridging social capital resulted in increased access to resources, as well as maintenance of healthy food traditions in some cases. Bonding social capital was an internal resource, but also had the potential to inadvertently recreate internal power dynamics. Community developers need to be aware of this, while creating opportunities for community context and assets to drive project development.